Predictive models for gas-liquid two phase flows: investigating dependence on liquid phase viscosity - Fayyaz, Ahad (2023)
The effect of inclination angle of pipe test section and liquid viscosity of silicone oil on flow development (i.e. flow regimes and transitions) and flow characteristics are studied in this thesis. The flow characteristics that are studied include liquid holdup, structure velocity and structure frequency. Intermittent flows such as slug, cap bubbly and churn usually present a pattern in which a gas dominated structure is followed by a liquid dominated structure. For given set of superficial properties, the pattern repeats with a characteristic mean frequency.